2002
DOI: 10.1007/bf02976608
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of nk cytotoxicity, antimetastasis and elongation effect of survival time in b16-f10 melanoma cells by oregonin

Abstract: We investigated the antitumor activity of oregonin, a diarylheptanoid derivative purified from Alnus hirsuta Turcz, Betulaceae. Oregonin is a potential novel immunomodulator, which augments the activation of natural killer (NK) cells, and thereby leads to a powerful antitumor activity. To evaluate the cytotoxicity of oregonin against tumor cells, we examined the effectiveness of NK cells and determined that oregonin could increase NK cell cytotoxicity. This was confirmed by MTT assay. In addition, the survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…They exerted their versatile roles in the defense of pathogens like murine cytomegalovirus (MCMV) [21,22] . Several studies also reported that hepatic NK and NKT cell took part in the antimetastasis of tumor [23][24][25] . NK1.1 + cells were reported to involve in the pathogenesis of many diseases, like human immunodeficiency virus (HIV) infection and liver disease [26,27] .…”
Section: Discussionmentioning
confidence: 96%
“…They exerted their versatile roles in the defense of pathogens like murine cytomegalovirus (MCMV) [21,22] . Several studies also reported that hepatic NK and NKT cell took part in the antimetastasis of tumor [23][24][25] . NK1.1 + cells were reported to involve in the pathogenesis of many diseases, like human immunodeficiency virus (HIV) infection and liver disease [26,27] .…”
Section: Discussionmentioning
confidence: 96%
“…It has been shown that oregonin reveals anti-oxidant and anti-inflammatory effects, and antitumor-promoting effect [13,14,16]. Oregonin has been shown to reveal antioxidative effect through scavenging actions on superoxide and 1,1-diphenyl-2-picrylhydrazyl radical [15].…”
Section: Introductionmentioning
confidence: 98%
“…These compounds prevent the inducible nitric oxide synthase expression and nitric oxide production in RAW264.7 macrophages treated with lipopolysaccharide [8,9,11] and attenuate lipopolysaccharide-induced expression of cyclooxygenase-2 and production of prostaglandin E and cytokines [9,13]. Oregonin increases the toxicity of natural killer cells against B16-F10 melanoma cell lines [12]. Hirsutenone has been shown to inhibit the tumor promoter 12-O-tetradecanoylphorbol-13-acetateinduced upregulation of cyclooxygenase-2 and matrix metalloproteinase-9 in human mammary epithelial MCF 10A cell lines [15].…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacologically active diarylheptanoids such as oregonin and hirsutenone are isolated from Alnus hirsuta Turcz, Alnus japonica and Alnus formosana [7][8][9] and have been shown to possess anti-inflammatory and anti-tumor effects [9][10][11][12][13][14]. These compounds prevent the inducible nitric oxide synthase expression and nitric oxide production in RAW264.7 macrophages treated with lipopolysaccharide [8,9,11] and attenuate lipopolysaccharide-induced expression of cyclooxygenase-2 and production of prostaglandin E and cytokines [9,13].…”
Section: Introductionmentioning
confidence: 99%